LEGAL PROTECTION FOR PLANTATION LAND USE STUDY OF CONFLICT BETWEEN THE CENTRAL LOMBOK WITH PT. PERKEBUNAN KOPI TRESNO KENANGAN - Giri, I Nyoman Nelson (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
Legal issues under discussion in this thesis is a dispute between the company PT. Perkebunan Kopi Tresno Kenangan Central Lombok district caused by the differences of perception with regard to the implementation of normative law against land use policies for the development of the plantation business.  How is the legal basis for guiding set of government policy in providing recommendations leasehold estate and for plantation companies in Central Lombok district, as well as how its safeguards. The author uses a normative legal research methods using a conceptual approach, legislation, and analytical approach, with the legal basis establishes guiding government policy in providing recommendations leasehold estates, such as: the 1945 Constitution, laws and legislation, Legislation with regard to agrarian resources, specifically land and other legislation relating to local government authorities as well as the terms and mechanisms of extension and renewal of the concession.With regard to the extension and renewal of the concession found this blurring of norms in childbirth which is very detrimental between them by letting the residents into the area of farmland. The absence of legal protection for the company from any conflict of norms in the form of wrong policy of the government of Central Lombok regency.Key Words : The right to the business, , Legal Protection